Liquid Chromatography Coupled with Linear Ion Trap Hybrid OrbitrapMass Spectrometry for Determination of Alkaloids in Sinomeniumacutum - Jinjun Shan; Xia Zhao; Cunsi Shen; Jianjian Ji; Jianya Xu; Shouchuan Wang; Tong Xie; Wenjun Tong (Molecules, 2018)
The characterization of alkaloids is challenging because of the diversity of structures and the complicated fragmentation of collision induced structural dissociation in mass spectrometry. In this study, we analyzed the alkaloids in Sinomenium acutum (Thunb.) Rehderet Wil by high resolution mass spectrometry. Chromatographic separation was achieved on a Phenomenex Kinetex C18 (2.1 mm × 100 mm, 2.6 μm) column with a mobile phase consisting of acetonitrile and water (0.1% formic acid) under gradient elution. A total of 52 alkaloids were well separated and 45 of them were structurally characterized, including morphinans, aporphines, benzylisoquinolines, and protoberberines. Specially, mass spectrometric study of the morphinan alkaloids were explicitly investigated. Electrostatic potential plot from simulation was calculated for determination of protonation sites. Further fragmentation analysis suggested that the C3H7N, CH4O, and H2O elimination was displayed in MS2 spectrum. These fragmentation pathways are universal for morphinan alkaloids having methoxy substituted cyclohexenone or cyclohexadienone moieties. Additionally, for nitrogen oxides, an ion-neutral complex intermediate is involved in the fragmentation process, generating additional oxygenated ions. All these results provided the universal rules of fragmentation used for detection of alkaloids, and will be expected to be highly useful for comprehensive study of multi-components in the herbal medicine analysis.